Peningkatan Ketrampilan Masyarakat untuk Budidaya Lebah Trigona-Itama (Stingless Bee) pada Lahan Pekarangan - Senoaji, Gunggung; Nuryatin, Nani; Hasan Lukman, Agung; Susanti, Elvi (Jurnal Ilmiah Pangabdhi, 2025)
The Pekarangan is the land around the house planted with various plants and animals. Pekarangan management needs to be done in order to provide economic and ecological benefits. One form of utilization of the yard is the cultivation of trigona-Itama bees. This activity aims to find out community knowledge about trigona bee cultivationThe method used was observing the pekarangan, preparing tools and materials, counseling, and demonstrating the cultivation of trigona bees. At the beginning of the activity, 60.7% of the community had seen the trigona-itama bee species, however, only 17.0% knew the benefits and results of trigona-itama; and there are no community that know the technique cultivating trigona-Itama bees. After this service activity, the community's knowledge about trigona bee cultivation increased, and they were able to apply their knowledge in their pekarangan. Trigona bees cultivation in the pekarangan will improve environmental quality through planting various bee food plants and producing healthy foods such as honey and propolis.